Memahami Persoalan Palestina-Israel dari Perspektif Islam - Suswanta, Suswanta (Jurnal Hubungan Internasional, 2012)
The difficulty in reconciling the Palestine and Israel conflict was because of political-ideology claims and theological claims. Theological claims in the conflict are very subjective and not easy to be solved by formal and structural diplomacy. The approach in theological side is the most dangerous engineered by Israel to occupy Palestine land. The effort to dismantle the engineering and imagination about the promised land as the form of scripture politicization still needs to be done until those facts become wider public discourse.